Effect of nanocrystalline hydroxyapatite implantation on the number of osteoblasts in bone healing post teeth extraction: Pengaruh implantasi hidroksiapatit nanokristalin terhadap jumlah osteoblas pada penyembuhan tulang pascaekstraksi gigi - Firdaus; Andreas Pascawinata; Rifka Annisa (Makassar Dental Journal PDGI Makassar, 2021)
Background: Extraction can cause alveolar bone resorption and slow bone healing. Post-extraction treatment is performed to help speed up the bone healing process. Objective: to determine the effect of nanocrystalline hydroxyapatite implantation on the number of osteoblasts in the post-extraction bone healing process. Method: By using laboratory experimental method and posttest only with control group design, the effect of treatment in the treatment group and the control group was measured using Wistar white male rats. Results: There was an effect of nanocrystalline hydroxyapatite implantation on the number of osteo-blasts on bone healing after tooth extraction of the rats on days 14 and 28. The highest mean number of osteoblasts was found in the treatment group on day 28. Discussion: Administration of nanocrystalline hydroxyapatite increased the number of osteo-blasts in bone healing after tooth extraction. Conclusion: Nanocrystalline hydroxyapatite implantation increases the formation of osteoblasts in bone healing after tooth extraction.